2021
DOI: 10.3390/en14144168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tip Leakage Flow on the Aerodynamic Performance and Stability of an Axial-Flow Transonic Compressor Stage

Abstract: To explain the effect of tip leakage flow on the performance of an axial-flow transonic compressor, the compressors with different rotor tip clearances were studied numerically. The results show that as the rotor tip clearance increases, the leakage flow intensity is increased, the shock wave position is moved backward, and the interaction between the tip leakage vortex and shock wave is intensified, while that between the boundary layer and shock wave is weakened. Most of all, the stall mechanisms of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…20 ; the vortex structures are displayed in color with dimensionless helicity. The Q criterion [ 35 ] is defined to capture the vortex edge; the Q criterion and dimensionless helicity [ 31 ] are defined as follows (Eq. (6) and Eq.…”
Section: Discussion and Analysis For Cfd Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 ; the vortex structures are displayed in color with dimensionless helicity. The Q criterion [ 35 ] is defined to capture the vortex edge; the Q criterion and dimensionless helicity [ 31 ] are defined as follows (Eq. (6) and Eq.…”
Section: Discussion and Analysis For Cfd Resultsmentioning
confidence: 99%
“…8 displays the tangential velocity distribution in the section near the 33 %, 55 %, and 72 % chord lengths of the rotor under the peak efficiency conditions. The experimental data were measured by the laser Doppler velocimeter discussed in literature [ [31] , [32] , [33] ]. The comparison revealed that the shock wave positions obtained from the experiments and numerical calculations were consistent and the main TLF, and the shock location before and after the shock were accurately predicted.…”
Section: Calculation Setting and Investigate Compressor Structurementioning
confidence: 99%
“…The paper conducts a numerical investigation on the rotor blades using NASA Stage 35 [26][27][28] as the research subject. NASA Stage 35 consists of 36 rotor blades and 46 stator blades.…”
Section: Research Object's Geometric Parametersmentioning
confidence: 99%